Higher Education Development Planning: Collaborative Strategies for Key Performance Indicator (KPI) Success - Wijayanto, Andhi; Wartini, Sri; Wicaksari, Erisa Aprilia (JEJAK, 2024)
This study aims to identify strategies for improving the achievement of Key Performance Indicator (KPI) 2 related to the Merdeka Belajar Kampus Merdeka (MBKM) program in the Management Study Program at Universitas Negeri Semarang (UNNES). KPI-2 focuses on increasing student participation in off-campus activities, such as internships, student exchange programs, and humanitarian projects. The study adopts a qualitative approach, utilizing SWOT analysis and QSPM to examine both internal and external factors affecting the implementation of the MBKM program. The findings reveal that while the Management Study Program has a relevant curriculum and is supported by ministerial policies, challenges such as limited types of MBKM activities and competition with students from other universities remain obstacles. Based on the analysis, the integration of the MBKM program with faculty research project assistance activities is proposed as a strategy to enhance student participation. The implementation of this strategy is expected to improve the achievement of KPI-2 for the Management Program at UNNES and serve as a reference for other study programs in executing MBKM.